(untitled) (International Congress on Economics, Management and Business Studies, 2026)
The transition to sustainable development has changed the role of accounting from a narrow financial recording system into a broader information infrastructure capable of capturing the economic consequences of environmental use, degradation, and restoration. Environmental cost accounting has therefore become an essential component of modern management and policy design because it helps organizations identify, measure, classify, and allocate environmental costs that are often hidden within overheads or dispersed across production processes. International practice increasingly connects environmental accounting with environmental management accounting (EMA), material flow cost accounting (MFCA), sustainability disclosure systems, and natural capital accounting. The International Federation of Accountants defines EMA as a framework that supports professional accountants and organizations in identifying and using both physical and monetary environmental information, while ISO 14051 formalizes MFCA as a method for tracing material flows and attaching cost values to both product output and material losses. At the macro level, the United Nations’ System of Environmental-Economic Accounting (SEEA) provides an internationally recognized framework for linking ecosystems, environmental assets, and economic activity. At the disclosure level, IFRS S2 requires organizations to report climate-related risks and opportunities that could affect cash flows, access to finance, and cost of capital.